TINJAUAN HUKUM EKONOMI SYARI’AH TERHADAP PENGGUNAAN KANTONG PLASTIK DALAM JUAL BELI DI PASAR TANJUNG BAJURE SUNGAI PENUH - Rifqi Nurdiansyah; Doli Witro (IAIN Syekh Nurjati Cirebon, 2022)
The trend of plastic waste is almost found in various parts of Indonesia, including Sungai Penuh City, Jambi Province. On the one hand, it must be acknowledged that plastic can be obtained easily in the buying and selling process. At the Tanjung Bajure Sungai Penuh market, plastic bags are not set at a price or, in other languages, are given free of charge. On the other hand, it can then be obtained easily, of course, it does not make plastic bags that can still be used and thrown away. The large amount of plastic waste found in the Sungai Penuh, especially in the river, is an indication that people still consider plastic a trivial matter and do not yet have high ecological awareness. Therefore, buying and selling that opens the way or provides opportunities for environmental damage needs to be explored and studied further to get a better solution for the sale and purchase. This study aims to review the sharia economic law on the services of traders providing plastic bag services to buyers at the Tanjung Bajure Market, Sungai Penuh. This type of research uses a qualitative approach. The primary data in this study is data obtained employing interviews and observations, and it is possible to use the Focus Group Discussion (FGD) method. Secondary data is obtained from library data such as books, classic scholarly books, scientific articles, research reports, internet websites, etc. related to the research topics discussed. Technical data analysis uses data reduction, data presentation, and drawing conclusions. The results of the study show a review of sharia economic law on the services of traders who provide plastic bag services to buyers at the Tanjung Bajure Market, Sungai Penuh as long as there is awareness to dispose of plastic bag waste in its place or recycle the plastic bag so that it does not cause damage and environmental pollution, then it is permissible. This is done by looking at the level of benefit from the benefits of the plastic bag.